Use of non-human primate hepatocytes for in vitro study of the pre-erythrocytic stages of malaria parasites. - Millet, P. (World Health Organization, 1990)
Methods were developed that allow invasion of sporozoites from simian malaria parasite species (Plasmodium cynomolgi, P. knowlesi, P. coatneyi, P. inui, P. gonderi, P. fragile) and development to schizont stages in rhesus and Saimiri monkey hepatocytes. The P. cynomolgi-rhesus monkey model was used to study inhibition of schizont development using monoclonal antibodies (MAbs) produced against the circumsporozoite (CS) protein of various strains and species of malaria parasites. Immunoelectron microscopy, using gold-labelled MAbs and cultured parasites, demonstrated that the CS protein persists in 7-day old liver stages of P. cynomolgi, but is not expressed at the surface of infected hepatocytes. A rhesus monkey was immunized with autologous hepatocytes (collected by biopsy) infected in vitro with liver stages of P. cynomolgi. This immunization elicited antibodies reacting with sporozoite, liver stage, and blood-stage parasites. In addition, human malaria parasites (P. falciparum, P. vivax, P. malariae) have been cultured in Saimiri or rhesus monkey hepatocytes. The P. vivax-Saimiri monkey model was used to study inhibition activity of sera from Saimiri monkeys experimentally immunized with recombinant P. vivax CS proteins. Post-immunization sera inhibited the parasite development, thus demonstrating the induction of antibodies effective against sporozoites. No relationship, however, was detected between in vitro inhibition and in vivo protection or antibody titres determined by ELISA or IFA.